Violence, restorative justice and forgiveness : dyadic forgiveness and energy shifts in restorative justice dialogue /: dyadic forgiveness and energy shifts in restorative justice dialogue. (2018) - Armour, Marilyn Peterson; Umbreit, Mark S, 1949-
No abstract available